A Patient with Suspected Diphtheria - Arfijanto, Muhammad Vitanata; Mashitah, Siti Irma; Widiyanti, Prihartini; Bramantono, Bramantono (Indonesian Journal of Tropical and Infectious Disease, 2010)
It was reported that a mature woman, Mrs. S, 42 years old with several complaints and symptoms such as fever, swallowing painweak body, swollen tonsil with beslag, dirty uvula of mouth cavity and tongue, and bullneck. The final diagnosis indicated that thepatient was suspected diphtheria, candidiasis oris, sepsis, and pneumonia. The sudden death of the patient was probably caused bymyocarditis.